Does Complexity Audit Task, Time Deadline Pressure, Obedience Pressure, and Information System Expertise Improve Audit Quality? - Wijaya, Inyoman Agus; Yulyona, Mentari Tri (International Journal of Economics and Financial Issues, 2017)
A survey of 216 auditors was conducted to investigate about the potential determinants of audit quality. This study using multiple linear regression technique. We find that complexity audit task, obedience pressure and information system expertise positively related to audit quality. This finding suggest that complexity audit task, obedience pressure and information system expertise play a significant part to improve the quality of audit. Further, complexity audit task and obedience pressure from superior can not make auditor fails to complete the required work and they remains improve audit quality. This study also find that there is no significant effect of time deadline pressure on audit quality. Information system expertise will greatly helpful auditors to expedite the auditing (shorten the time of the auditing) and will be useful in determination of audit procedures, so that can reduce the complexity of task and, in turn, can produce a quality audit reports. Keywords: complexity audit task; time deadline pressure; obedience presure; information system expertise; audit quality. JEL Classifications: M42, M51, M15